PENGGUNAAN METODE TUSUK SATE BERBASIS MEDIA REALIA PALSTISIN UNTUK MENINGKATKAN PEMAHAMAN KONSEP PEMBAGIAN PADA PEMBELAJARAN MATEMATIKA SISWA KELAS III SD - Rudy Hartono Pohan; Nur 'Afifah (STKIP Subang, 2026)
This study aims to improve the understanding of division concepts in third-grade elementary school students' mathematics learning through the use of a skewer method based on plastisin realia media. The research uses a classroom action research approach carried out in two cycles. The results of the study indicate that this method is able to increase students' interest, activeness, and learning outcomes. Learning completeness increased from a pre-cycle of 40% to 60% in cycle I and 95% in cycle II. The class average score also increased from 54.50 in the pre-cycle to 67.25 in cycle I and 86.50 in cycle II. Thus, the skewer method based on plastisin realia media is effective in improving students' understanding of division concepts